Green Chemistry: The Role of Green Chemistry in Sustainable Chemical Industry (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Green Chemistry is the utilization of a set of principles that reduces or eliminates the use or generation of hazardous substances. It applies across the life cycle of a chemical product including its design, manufacture, use and ultimate disposal. It is also known as sustainable chemistry. To meet the demands of modern civilization, we need varieties types of chemical products and chemical industries. These very often lead to the formation of hazardous substances and sometimes we are also to use the hazardous substances. To prevent or minimize the formation and use of such hazardous substances, the chemists are required to develop the novel technologies. This need has inspired the generation of the new branch of chemistry called Green chemistry which follows the principle “Prevention is better than cure”